Pendugaan Umur Simpan Bubuk Kopi Arabika Menggunakan Metode Arrhenius dengan Kemasan Aluminium Foil dan Plastik (Polipropilen) - Elida Novita; Dian Purbasari; M. Syahrul Munir Mubarok (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The storage method is one way to maintain coffee quality. Storage with aluminum foil and plastic (PP) packaging is an effective and safe technology to protect coffee grounds. Specialty coffee powder cannot be accepted if the organoleptic score is below 80, for that it is necessary to estimate the shelf life. This study aims to analyze the quality degradation of Bondowoso arabica coffee powder based on specialty standards using the SCAA protocol during storage with aluminum foil packaging and compare it with plastic packaging (PP) and estimated the shelf life of Bondowoso arabica ground coffee products based on flavor value parameters using the arrhenius method. Coffee powder quality degradation with plastic packaging (PP) is faster than aluminum foil packaging. This is because plastic packaging on the fourth day with a temperature of 40°C is not meet specialty standards. The greater the temperature used, the greater the decrease in quality. The shelf life of coffee powder uses aluminum foil packaging, which is 3 days at 40°C, 2 days at 50°C, and 1.3 days at 60°C. Whereas with plastic packaging (PP), the shelf life is shorter, which is 2 days at 40°C, 1.2 days at 50°C and 1 day at 60°C. Keyword: accelerated Shelf-Life Testing (ASLT), aluminum foil, arabica coffee, packaging, shelf